Shazam! - Johns, Geoff 1973-; Frank, Gary 1969-; Anderson, Brad 1924-2015 (DC Comics, 2013)
Fifteen-year-old orphan Billy Batson has been selected to wield ancient powers, but these same powers are sought by the villainous Black Adam, and he will do anything to obtain them
"Originally published in single magazine form as Justice League 7-11, 0,14-16, 18-21.
Keywords: Justice League of America; Waisenkind; Junge